Clinical evaluation of crown and bridge prosthesis placed in patients attended in the Bangabandhu Sheikh Mujib Medical University (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
The proper diagnosis and clinical assessment are essential when dealing with the complications of fixed restorations in dental prosthesis. This cross-sectional study was carried out to evaluate clinically the crown and bridge prosthesis among the patients attending in the Department of Prosthodontics, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. A total of 50 patients with full veneer crowns or bridges were selected. Clinical assessment for the contour of the prosthesis, nature of the contact of the prosthesis, type of occlusal contact in ICP were done. Among the study subjects, 44% and 52% of the prostheses were over-contoured buccally and lingually, respectively. The prostheses contacted with adjacent tooth mesially at occlusal one-third in 58%, middle one-third in 40% & cervical one-third in 2% cases. The prostheses contacted with adjacent tooth distally at occlusal one-third in 52%, middle one-third in 44% & nothing abnormality detected in 4%. About half of prostheses (54%) contacted with an opposite tooth at the level of central fossa whereas 40% at buccal to central fossa and only a few numbers (6%) at lingual/palatal to central fossa. The nature of proximal contact was normal in 52%, tight in 36%, and open in 12% of the prostheses. As the prostheses cemented in the patient's mouth were not up to the accepted clinical standards, so enrichment of knowledge about prosthetics are needed and responsibilities should be ensured.BSMMU J 2022; 15(2): 80-83